Symbiotic compatibility between rice cultivars and arbuscular mycorrhizal fungi genotypes affects rice growth and mycorrhiza-induced resistance - Guigard, Ludivine; Jobert, Lea; Busset, Nicolas; Moulin, Lionel; Czernic, Pierre (Frontiers in Plant Science, 2023)
Arbuscular mycorrhizal fungi (AMF) belong to the Glomeromycota clade and can form root symbioses with 80% of Angiosperms, including crops species such as wheat, maize and rice. By increasing nutrient availability, uptake and soil anchoring of plants, AMF can improve plant's growth and tolerance to abiotic stresses. AMF can also reduce symptoms and pathogen load on infected plants, both locally and systemically, through a phenomenon called mycorrhiza-induced resistance (MIR). There is scarce information on rice mycorrhization, despite the high potential of this symbiosis in a context of sustainable water management in rice production systems. We studied the symbiotic compatibility (global mycorrhization & arbuscules intensity) and MIR phenotypes between six rice cultivars from two subspecies (indica: IR64 & Phka Rumduol; japonica: Nipponbare, Kitaake, Azucena & Zhonghua 11) and three AMF genotypes (Funneliformis mosseae FR140 (FM), Rhizophagus irregularis DAOM197198 (RIR) & R. intraradices FR121 (RIN)). The impact of mycorrhization on rice growth and defence response to Xanthomonas oryzae pv. oryzae (Xoo) infection was recorded via both phenotypic indexes and rice marker gene expression studies.All three AMF genotypes colonise the roots of all rice varieties, with clear differences in efficiency depending on the combination under study (from 27% to 84% for Phka Rumduol-RIN and Nipponbare-RIR combinations, respectively). Mycorrhization significantly (α=0.05) induced negative to beneficial effects on rice growth (impact on dry weight ranging from -21% to 227% on Azucena-FM and Kitaake-RIN combinations, respectively), and neutral to beneficial effects on the extent of Xoo symptoms on leaves (except for Azucena-RIN combination which showed a 68% increase of chlorosis). R. irregularis DAOM197198 was the most compatible AMF partner of rice, with high root colonisation intensity (84% of Nipponbare's roots hyphal colonisation), beneficial effects on rice growth (dry weight +28% (IR64) to +178% (Kitaake)) and decrease of Xoo-induced symptoms (-6% (Nipponbare) to -27% (IR64)). Transcriptomic analyses by RT-qPCR on leaves of two rice cultivars contrasting in their association with AMF show two different patterns of response on several physiological marker genes. Overall, the symbiotic compatibility between rice cultivars and AMF demonstrates adequate colonization, effectively restricting the nutrient starvation response and mitigating symptoms of phytopathogenic infection.